Cross-sectional survey of asymptomatic malaria in Dak Nong province in the Central Highlands of Vietnam for the malaria elimination roadmap. - Huynh Hong Quang (Public Library of Science (PLoS), 2021)
Asymptomatic parasite carriers represent a "silent" infective reservoir for malaria transmission and contributes to malaria persistence. However, limited data are available on asymptomatic malaria in Vietnam. Between November 2018 and March 2019, we conducted a malaria epidemiological survey of asymptomatic people (children ≥ 10 years old and adults ≥18 years old, n = 2,809) residing in three communes in Tuy Duc district, Dak Nong province in the Central Highlands of Vietnam. Based on the national stratification of malaria risk, Dak Buk So, Dak Ngo and Quang Truc communes were classified by the National Malaria Control Programme as low, moderate and high malaria endemic areas, respectively. Using participants' finger prick blood samples, malaria parasites were detected by one-step reverse transcription-quantitative polymerase chain reaction (RT-qPCR). The median age (Interquartile Range) for adults and children were 35 years (26-50) and 12 years (11-14), respectively. The prevalence of asymptomatic malaria was 1.7% (22/1,328), 3.5% (31/890) and 12.2% (72/591) for participants from Dak Buk So, Dak Ngo and Quang Truc, respectively. The prevalence of asymptomatic malaria was lower in children compared to adults: 2.6% (9/352) versus 4.7% (116/2,457) (Odds Ratio 0.53, 95% Confidence Interval 0.28 to1.02). Ownership of long-lasting insecticide-treated bed nets and hammocks was 97.1%, 99.0% and 94.7% for participants in Dak Buk So, Dak Ngo and Quang Truc, respectively, however, only 66.0%, 57.3% and 42.8% of the participants reported using bed nets every night. Of the several risk factors examined, going to the forest two weeks prior to enrolment into the study and sleeping in the forest had a significant association with participants being infected with asymptomatic malaria in Quang Truc, but not in the other two communes. Knowledge of the prevalence and distribution of asymptomatic malaria will help design and evaluate future intervention strategies for malaria elimination in Vietnam.